(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: As a critical organ of the avian digestive system, the liver is involved in metabolism, detoxification, bile production, and the synthesis of proteins. It is an organ that typically appears bilateral in birds, being positioned ventrally to the body cavity. The right lobe is usually larger than the left in most species. The color and structure of the liver, and the presence or absence of a gallbladder, depend on species, diet, and physiology. Materials and Methods: This review is based on an analysis of morphological and histological data from research conducted on livers of various Iraqi birds. The data included anatomical descriptions, lobular organization, vascular organization, and histological characteristics of the liver such as hepatocyte organization and sinusoidal structure. Results: The reviewed data show that in Iraqi birds, the avian liver is bilobed, encapsulated in connective tissue (Glisson’s capsule), and divided into lobules that vary in distinctness. Hepatocytes are polygonal in shape and organized in cords surrounding the central vein; sinusoids are lined by endothelial and Kupffer-like cells. The portal triad includes the hepatic artery, portal vein, bile duct, and lymphatic vessels. Conclusion: The morphological and histological characteristics of the livers from Iraqi birds show both uniformity of structure as well as species differences. These differences reflect ecological adaptations, dietary habits, and evolutionary traits. Understanding these liver features provides essential insights into avian physiology, health, and comparative anatomy among Iraqi bird species.